2022
DOI: 10.3390/ijerph191811766
|View full text |Cite
|
Sign up to set email alerts
|

Scales and Historical Evolution: Methods to Reveal the Relationships between Ecosystem Service Bundles and Socio-Ecological Drivers—A Case Study of Dalian City, China

Abstract: Ecosystem service (ES) bundles can be defined as the temporal and spatial co-occurrence of ESs. ES bundles are jointly driven by socio-ecological factors and form at different scales. However, in recent research, a few studies have analyzed the dynamic evolution and driving mechanisms of ES bundles at different scales. Therefore, this study explored the spatial patterns of six ESs supplied in Dalian (China) from 2005 to 2015 at three spatial scales, determining the distribution and evolution patterns of ES bun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…This provides decision-makers with a more comprehensive and long-term perspective, avoiding the blind implementation of ecological restoration measures. We found that pollination, habitat provision, and carbon sequestration services have formed a stable bundle (ESB I) over the past 20 years, as they are closely related to high vegetation cover [50,51]. Water production and soil conservation services form ESB III and are mainly determined by rainfall [52].…”
Section: The Role Of Esbs In Ecological Restorationmentioning
confidence: 92%
“…This provides decision-makers with a more comprehensive and long-term perspective, avoiding the blind implementation of ecological restoration measures. We found that pollination, habitat provision, and carbon sequestration services have formed a stable bundle (ESB I) over the past 20 years, as they are closely related to high vegetation cover [50,51]. Water production and soil conservation services form ESB III and are mainly determined by rainfall [52].…”
Section: The Role Of Esbs In Ecological Restorationmentioning
confidence: 92%